A stakeholder perspective of corporate social responsibility - Otis, Esther (Kansas State University, 2010)
The adoption of a corporate social responsibility (CSR) policy affords a company with the opportunity to engage with stakeholders in a manner that is not necessarily tied directly to a company’s business as usual. CSR research has burgeoned in the last several decades, keeping pace with companies worldwide and their steady incorporation of CSR policies into their business models. To that end, research has been primarily focused on CSR policy perception from external stakeholders or managers. This research project examines the sensemaking processes related to an environmental sustainability-related CSR policy among a diverse group of internal stakeholders at a mid-sized electric utility company. An analysis of the data suggests that hierarchical divisions of employees are non-existent when the CSR policy is enduring, consistent, and upholds company values. Moreover, employee enactment of CSR policies operates as a mechanism whereby employees internalize the promoted corporate values. Such environmental CSR policies tacitly reinforce an organization’s cultural values among its employees. Additionally, environmentally sustainable CSR policies supported by environmentally exhausting companies induce a minimal justification hypothesis when dissonance is present between the nature of a company’s industry and practices related to sustaining the environment.
Keywords: Corporate Social Responsibility; environmental sustainability; stakeholder theory; organizational values; Speech Communication (0459)